Exercícios Físicos para Mulheres com Varizes : Treinar condicionamento geral ou membros inferiores? - Carvalho, Icaro do Carmo; Ferreira, Daniela Karina da Silva (2021)
This study compared the effect of two training programs on physical fitness and quality of life in women with varicose veins, one being a general fitness program (CFG) and the other for strengthening lower limbs (MMII by its acronym in Portuguese) applied to 2 groups of volunteers, regular practitioners of physical exercise, for a period of 12 weeks. Data about quality of life, calf perimeter, ankle goniometry, heel rise test and step test were collected, pre and post training. Nine women from the CFG program (54 ± 18 years) and eleven from the MMII program (58 ± 8 years) completed the intervention. Comparing the magnitude of variation in the results of each test and between the programs by independent t-test, the participants in the MMII program showed better performance in the tests of physical fitness and quality of life than those of the CFG program, with a significant difference in the results of muscular endurance (p <0.01 for repetitions and p = 0.02 for execution time in the toe test) and flexibility (p <0.01). It was concluded that a specific program to strengthen lower limbs allows better results in physical fitness compared to a general conditioning program.
Esse estudo comparou o efeito de dois programas de treinamento sobre a aptidão física e qualidade de vida em mulheres com Varizes, sendo um programa de condicionamento físico geral (CFG) e o outro de fortalecimento de membros inferiores (MMII) aplicado a 2 grupos de voluntárias, praticantes regulares de exercício físico, por 12 semanas. Foram coletados, pré e pós treinamento, dados de qualidade de vida, perimetria de panturrilha, goniometria do tornozelo, teste de ponta de pé e degrau. Nove mulheres do programa CFG (54 ± 18 anos) e onze do programa MMII (58 ± 8 anos) concluíram a intervenção. Comparando a magnitude de variação nos resultados de cada teste e entre os programas por teste t independente, as participantes do programa MMII apresentaram melhor desempenho nos testes de aptidão física e qualidade de vida que as do programa CFG, com diferença significativa nos resultados de resistência muscular (p < 0,01 para repetições e p = 0,02 para tempo de execução no teste de ponta de pé) e flexibilidade (p < 0,01). Concluiu-se que um programa específico de fortalecimento de membros inferiores possibilita melhores resultados em aptidão física em relação a um programa de condicionamento geral.
Keywords: Varicose Veins; Muscle Strength; Physical Fitness; Varizes^lpt; Força Muscular; Aptidão Física